Evaluating an information system to provide creative guidance about health-and-safety in manufacturing. Issue 11 (18th August 2021) - Maiden, Neil; Zachos, Konstantinos; Lockerbie, James
ABSTRACT: Creativity's importance to organisations and businesses is now recognised to be a precondition for both design and innovation. One strategy is to introduce new forms of information system that support human creative thinking by their employees. Most successful uses have been in professional disciplines in the creative industries such as design and theatre. This paper reports the design and evaluation of a new information system that was researched and developed to support human creativity in a non-creative industry – health-and-safety in a manufacturing plant. An established risk detection and resolution process in one plant was extended with the new system to support plant employees to think creatively about resolutions to health-and-safety risks. The new system was used in a manufacturing plant for over 3 months. Results revealed that a subset of the risk resolutions generated with the new system were more creative and more complete than risk resolutions generated without the system in a corresponding period. However, the employees needed more time than was available to generate more complete risk resolutions. The evaluation results led to coordinated changes to both the information system and work practices associated with it.